Descriptions of a new Aedes species and subspecies of the subgenus Aedimorphus, from southwest Cameroon and updated key for the species of the “Domesticus group” - Kowo, Cyril; Mayi, Marie Paul Audrey; de Almeida, Antonio Paulo Gouveia; Foncha, David; Elad, Mirabel; Andongma, Esack; Nota Anong, Damian; Djomo, Charlene; Fru-Cho, Jerome; Sehgal, Ravinder; Cornel, Anthony John (African Entomology, 2023)
Male specimens of Aedes stenostylus Cornel, Kowo & Mayi sp. nov. and Aedes leptolabis ssp. talangayensis Cornel, Kowo & Mayi sp. nov. are described. They were collected mainly by sweep netting through forest floor vegetation in partially logged areas and in the surrounding pristine forest (Talangaye Forest) in the Nguti Subdivision in the south-west region of Cameroon. An updated key of the Aedimorphus “Domesticus group” species, based on the morphology of the male genitalia is provided.